A Feira da Cidade Nova IV como território de aprendizagem no Ensino Médio: experiência didática na E. E. E. F. M. Luiz Nunes Direito (Ananindeua-PA) - CHAVES, Camila da Costa (2024)
This work will discuss the knowledge and territoriality of the Cidade Nova IV fair, located in Ananindeua-PA, as a study strategy for students from class 103 of the First Year of High School with the discipline Integrator Project, from E. E. E. F. M. Luiz Nunes Direito and the scholarship holders from the Institutional Teaching Initiation Scholarship Program – PIBID. At the popular fair it is possible to see the best that each region has to offer, and also get to know a little about the culture through it. The methodology adopted for this monograph was based on bibliographical research on the history of the fair and interviews with stallholders to learn a little about their trajectories. This course conclusion article's main objective is to show the Cidade Nova IV fair as a territory of resistance and learning in high school that took place at the school. The research generated the production of a documentary with multiple regional and identity lessons for the scholarship holders, students and the entire school community, and which has great potential to be used in the high school classroom as an aid in academic and civic education.